RAS/RAF/MEK/ERK and PI3K/PTEN/AKT Signaling in Malignant Melanoma Progression and Therapy - Ichiro Yajima; Mayuko Y. Kumasaka; Nguyen Dinh Thang; Yuji Goto; Kozue Takeda; Osamu Yamanoshita; Machiko Iida; Nobutaka Ohgami; Haruka Tamura; Yoshiyuki Kawamoto; Masashi Kato (Dermatology Research and Practice)
Cutaneous malignant melanoma is one of the most serious skin cancers and is highly invasive and markedly resistant to conventional therapy. Melanomagenesis is initially triggered by environmental agents including ultraviolet (UV), which induces genetic/epigenetic alterations in the chromosomes of melanocytes. In human melanomas, the RAS/RAF/MEK/ERK (MAPK) and the PI3K/PTEN/AKT (AKT) signaling pathways are two major signaling pathways and are constitutively activated through genetic alterations. Mutations of RAF, RAS, and PTEN contribute to antiapoptosis, abnormal proliferation, angiogenesis, and invasion for melanoma development and progression. To find better approaches to therapies for patients, understanding these MAPK and AKT signaling mechanisms of melanoma development and progression is important. Here, we review MAPK and AKT signaling networks associated with melanoma development and progression.